The Study of Bound Water Status and Pore Size Distribution of Chinese Fir and Poplar Cell Wall by Low-Field NMR - Huimin Cao; Jianxiong Lyu; Yongdong Zhou; Xin Gao (International Journal of Polymer Science)
With the increasing shortage of timber resources and the advancement of environmental protection projects, many artificial fast-growing forests are planted and used as raw materials in China. There are significant differences in the properties of natural forest wood and artificial fast-growing forest wood, and the properties of wood mainly depend on the change in the status of bound water in the cell wall. In this study, the fiber saturation point (FSP) and pore size distributions within the cell wall of six species of fast-growing forest wood were studied by low-temperature nuclear magnetic resonance (NMR) technology. The effects of species, growth rings, and extractives on the FSP and pore structure were analyzed. The water vapor sorption experiments were performed, and the adsorption isotherms of the samples were fitted through the Guggenheim-Anderson-de Boer (GAB) equation. According to the least-square regression of the adsorption isotherms and combined with the low-temperature NMR experiments, the content and proportion of the different types of bound water were analyzed. The results showed that the average FSP of each Chinese fir was about 40% and that of each poplar was about 35%. There is about a 10% difference between the FSP measured by NMR technology and the adsorption bound water content obtained by adsorption isothermal. The pore size distribution results show that in all samples, the proportion of pores larger than 10.5 nm is very low, about 10%; the proportion of 1.92-10.5 nm pores is about 30%; and the proportion of pores smaller than 1.92nm is more than 50%. This work will be helpful to the study of the wood moisture status and provide reference data for wood modification.